A model of dry bean growth and development cultivar carioca - Villacorta, Amador; Gutierrez, Andrew Paul; Guimarães, Maria de Fátima; Carnajal, Blanca Luz Pinilla; Miglioranza, Edison (Pesquisa Agropecuaria Brasileira, 2014)
A simulation model for the dry bean (Phaseolus vulgaris L.) indeterminate large guide (type III), cv. carioca is presented and is used to examine the priorities and allocation dynamics of photosynthate. The model is valid for the data of Londrina, PR.
Keywords: plant modeling; stochastic model; population dynamics